Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/anbr.202100060
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B Lymphocytes Using Protein‐Functionalized Graphene Oxide

Abstract: The high surface area and the possibility of surface functionalization associated with a high biocompatibility endow graphene oxide with a great potential for biomedical applications. Although this material has been widely investigated for cancer therapy, it has been scarcely used for the treatment of autoimmune diseases. Herein, graphene oxide–lysozyme stable conjugates are prepared by a straightforward noncovalent functionalization approach. The complexes are able to selectively target a B lymphocyte cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently, Muzi functionalized GO with hen egg lysozyme (HEL) through a simple non-covalent conjugation method and used the nanocarrier for the selective targeting of B lymphocytes in autoimmune diseases. It was suggested that the same process could be used for other proteins or peptides capable of targeting certain new B cells ( Muzi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Muzi functionalized GO with hen egg lysozyme (HEL) through a simple non-covalent conjugation method and used the nanocarrier for the selective targeting of B lymphocytes in autoimmune diseases. It was suggested that the same process could be used for other proteins or peptides capable of targeting certain new B cells ( Muzi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…GO has benefited manyfold in sensing applications: firstly, GO coating attracts reproducibly and homogeneously a large fraction of the molecules in the proximity of the hot spots thanks to the combination of a hydrophobic structure with oxygenated surface functional groups. The GO-lysozyme interaction is so strong that recently GO-lysozyme bio-conjugates have been proposed as nanocarriers for the targeted therapy of B-cell-mediated autoimmune diseases [44]. Secondly, the GO veil can be readily prepared by direct physisorption on the nanoparticles' assembly with precise control of surface coverage and thickness as opposed to complex vapor deposition techniques often used for graphene.…”
Section: Introductionmentioning
confidence: 99%